If $\tan \beta = \cos \theta \tan \alpha ,$ then ${\tan ^2}\frac{\theta }{2} = $
$\frac{{\sin (\alpha + \beta )}}{{\sin (\alpha - \beta )}}$
$\frac{{\cos (\alpha - \beta )}}{{\cos (\alpha + \beta )}}$
$\frac{{\sin (\alpha - \beta )}}{{\sin (\alpha + \beta )}}$
$\frac{{\cos (\alpha + \beta )}}{{\cos (\alpha - \beta )}}$
${\cos ^2}A{(3 - 4{\cos ^2}A)^2} + {\sin ^2}A{(3 - 4{\sin ^2}A)^2} = $
If $\cos \theta = \frac{3}{5}$ and $\cos \phi = \frac{4}{5},$ where $\theta $ and $\phi $ are positive acute angles, then $\cos \frac{{\theta - \phi }}{2} = $
If $cosA + cosB = cosC,\ sinA + sinB = sinC$ then the value of expression $\frac{{\sin \left( {A + B} \right)}}{{\sin 2C}}$ is
Prove that $\tan 4 x=\frac{4 \tan x\left(1-\tan ^{2} x\right)}{1-6 \tan ^{2} x+\tan ^{4} x}$
Prove that $\frac{\cos 9 x-\cos 5 x}{\sin 17 x-\sin 3 x}=-\frac{\sin 2 x}{\cos 10 x}$